Comparison between Hypericum triquetrifolium Leaves and Derived Calli in Essential Oil Content - Azeez, Hoshyar A (Al-Nahrain Journal of Science, 2017)
The analysis of essential oil using the in-tube extraction technique (ITEX) from the plant leaves and derived calli (fresh calli, dry calli and cell suspension culture) of Hypericum triquetrifolium Turra., initiated from leaves. The plant grows wild in Kurdistan region of Iraq. Studied parameters were determined using in-tube extraction coupled with gas chromatography - mass spectrometry system (ITEX/ GC-MS). A total of 33 compounds were identified as essential oils in leaves, the dominant constituents were measured such as Hexenal, (E) (12.63%), Octane, 2,3,3-trimethyl (11.36%), Pentadecane, 7-methyl- (9.7%), Undecane (6.15%) and alpha. -Pinene (5.75%), while the analysis of fresh calli derived from leaves showed 22 types of essential oil; Dodecane (23.78%), Nonane, 3-methyl- (10.45%), Limonene (9.68%), Furan, 2-pentyl-(9.11%), Toluene (8.18%) and Undecane (7.45%). On the other hand, 21 oil components were found in dry calli; the major compounds were identified as Limonene (17.18%), Undecane (12.21%), Beta.-Myrcene (5.51%) and Toluene (4.93%). However, only 23 oil components were determined in cell suspension culture, the main essential oils were; Undecan (42.92%), Octane, 2,4,6-trimethyl (13.71%), Oxirane, 2-(1,1-dimethylethyl)-3-methyl (9.84%), Limonene (6.69%) and Toluene (2.98%).